Retorika Digital dan Social Network Analysis Generasi Milenial Tionghoa melalui Youtube - Sinta Paramita; Lydia Irena (Jurnal Komunikasi, 2020)
The millennial generation of ethnic Chinese is a native digital generation that contributes to technological development. With strong skills and understanding in communicating creative messages through technology, the Chinese millennial generation also contributed to the development of Indonesia's digital culture. Technological developments have resulted in new jobs such as Youtube. Youtuber is someone who creates interesting audio-visual content so that the audience is interested and makes the content as entertainment or certain recommendations. By using the theory of rhetoric put forward by Aristotle, this study will look at the crowds of information flow in one content and see the strength of content as what was created to attract the attention of the audience. By using a quantitative approach through the Social Network Analysis (SNA) method. This study aims to describe the complexity of network communication in content and find out the digital rhetoric of the Chinese millennial generation that is currently developing in creating digital content. The results of the analysis show a high centralized value approaching 1, the results obtained in this study 0.052 indicate there is an account that dominates the information in the content. A density value of 0 indicates that there are no closely related accounts in the content. Reciprocity or reciprocal values 0 indicate that there is no two-way communication. The modularity or community values in the group 0.763 indicate that in the content there is a split network that cones to a certain account. The value of the diameter or the longest distance between network accounts reaches number 4, content with the power of deliberative rhetoric is proven to be able to attract the attention of the audience Generasi milenial etnis Tionghoa adalah generasi native digital yang turut berkontribusi pada perkembangan teknologi. Dengan kecakapan dan pemahaman yang kuat dalam mengkomunikasikan pesan-pesan kreatif melalui teknologi, generasi milenial Tionghoa pun berkontribusi pada pengembangan budaya digital Indonesia. Perkembangan teknologi telah menghasilkan pekerjaan baru salah satunya seperti Youtuber. Youtuber adalah seseorang yang menciptakan konten-konten audio visual yang menarik sehingga khalayak tertarik dan menjadikan konten tersebut sebagai hiburan atau rekomendasi tertentu. Dengan menggunakan teori retorika yang dikemukakan oleh Aristoteles, penelitian ini akan melihat keramaian arus informasi dalam satu konten dan melihat kekuatan konten seperti apa yang diciptakan untuk menarik perhatian khalayak. Dengan menggunakan pendekatan kuantitatif melalui metode Social Netwok Analysis (SNA). Penelitian ini bertujuan untuk menjabarkan kompleksitas komunikasi jaringan dalam sebuah konten dan mengetahui retorika digital generasi milenial Tionghoa yang berkembang saat ini dalam membuat konten digital. Hasil analisis menunjukkan Nilai sentralisasi tinggi mendekati 1, hasil yang diperoleh dalam penelitian ini 0.052 menunjukkan terdapat akun yang mendominasi informasi dalam konten tersebut. Nilai density atau kepadatan 0 menunjukkan tidak ada akun yang terhubung secara erat dalam konten tersebut. Nilai reciprocity atau timbal balik 0 menunjukkan tidak ada yang menunjukkan komunikasi dua arah. Nilai modulitas atau komunitas di dalam kelompok 0.763 menunjukkan bahwa di dalam konten tersebut terjadi perpecahan jaringan yang mengerucut kepada akun akun tertentu. Nilai diameter atau jarak terpanjang antara akun jaringan mencapai angka 4, Konten dengan kekuatan retorika deliberative terbukti dapat menarik perhatian khalayak.